Moderate dietary sodium restriction added to angiotensin converting enzyme inhibition compared with dual blockade in lowering proteinuria and blood pressure: randomised controlled trial. (26th July 2011) - Slagman, Maartje C J; Waanders, Femke; Hemmelder, Marc H; Woittiez, Arend-Jan; Janssen, Wilbert M T; Lambers Heerspink, Hiddo J; Navis, Gerjan; Laverman, Gozewijn D
Abstract : Objective To compare the effects on proteinuria and blood pressure of addition of dietary sodium restriction or angiotensin receptor blockade at maximum dose, or their combination, in patients with non-diabetic nephropathy receiving background treatment with angiotensin converting enzyme (ACE) inhibition at maximum dose. Design Multicentre crossover randomised controlled trial. Setting Outpatient clinics in the Netherlands. Participants 52 patients with non-diabetic nephropathy. Interventions All patients were treated during four 6 week periods, in random order, with angiotensin receptor blockade (valsartan 320 mg/day) or placebo, each combined with, consecutively, a low sodium diet (target 50 mmol Na + /day) and a regular sodium diet (target 200 mmol Na + /day), with a background of ACE inhibition (lisinopril 40 mg/day) during the entire study. The drug interventions were double blind; the dietary interventions were open label. Main outcome measures The primary outcome measure was proteinuria; the secondary outcome measure was blood pressure. Results Mean urinary sodium excretion, a measure of dietary sodium intake, was 106 (SE 5) mmol Na + /day during a low sodium diet and 184 (6) mmol Na + /day during a regular sodium diet (P<0.001). Geometric mean residual proteinuria was 1.68 (95% confidence interval 1.31 to 2.14) g/day during ACE inhibition plus a regular sodium diet. Addition of angiotensin receptor blockade to ACE inhibition reduced proteinuria to 1.44 (1.07 to 1.93) g/day (P=0.003), addition of a low sodium diet reduced it to 0.85 (0.66 to 1.10) g/day (P<0.001), and addition of angiotensin receptor blockade plus a low sodium diet reduced it to 0.67 (0.50 to 0.91) g/day (P<0.001). The reduction of proteinuria by the addition of a low sodium diet to ACE inhibition (51%, 95% confidence interval 43% to 58%) was significantly larger (P<0.001) than the reduction of proteinuria by the addition of angiotensin receptor blockade to ACE inhibition (21%, (8% to 32%) and was comparable (P=0.009, not significant after Bonferroni correction) to the reduction of proteinuria by the addition of both angiotensin receptor blockade and a low sodium diet to ACE inhibition (62%, 53% to 70%). Mean systolic blood pressure was 134 (3) mm Hg during ACE inhibition plus a regular sodium diet. Mean systolic blood pressure was not significantly altered by the addition of angiotensin receptor blockade (131 (3) mm Hg; P=0.12) but was reduced by the addition of a low sodium diet (123 (2) mm Hg; P<0.001) and angiotensin receptor blockade plus a low sodium diet (121 (3) mm Hg; P<0.001) to ACE inhibition. The reduction of systolic blood pressure by the addition of a low sodium diet (7% (SE 1%)) was significantly larger (P=0.003) than the reduction of systolic blood pressure by the addition of angiotensin receptor blockade (2% (1)) and was similar (P=0.14) to the reduction of systolic blood pressure by the addition of both angiotensin receptor blockade and low sodium diet (9% (1)), to ACE inhibition. Conclusions Dietary sodium restriction to a level recommended in guidelines was more effective than dual blockade for reduction of proteinuria and blood pressure in non-diabetic nephropathy. The findings support the combined endeavours of patients and health professionals to reduce sodium intake. Trial registration Netherlands Trial Register NTR675.